1982
DOI: 10.21273/jashs.107.2.330
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Light on Lily (Lilium longiflorum Thunb.). I. Influence of Light Intensity on Plant Development1

Abstract: Lily plants were exposed to natural daylight (ND), 50% ND (50% saran), ND plus 16 hours of incandescent (Inc) or ND plus 16 hours of high pressure sodium discharge (HID) lamp light at both University of Minnesota and Michigan State University. Light intensity had no significant horticultural effect on plant development rate that could not be readily explained by temperature. The Inc or HID light source hastened flowering by 5 to 8 days over the ND plants when given from emergence to flower. However, the rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
1

Year Published

1982
1982
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 4 publications
0
12
1
Order By: Relevance
“…However, differences in total flower bud number were small with a maximum increase for only 0.9 flower buds when plants were lighted from 30-40 days after E (Table 2). Heins, et al (9) found that during vegetative or early reproductive growth, neither con tinuous supplemental high intensity discharge (HID) lighting, nor 50% saran shading, influenced flower bud number. However, long term (30 day) Inc lighting reduced bud number (9).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, differences in total flower bud number were small with a maximum increase for only 0.9 flower buds when plants were lighted from 30-40 days after E (Table 2). Heins, et al (9) found that during vegetative or early reproductive growth, neither con tinuous supplemental high intensity discharge (HID) lighting, nor 50% saran shading, influenced flower bud number. However, long term (30 day) Inc lighting reduced bud number (9).…”
Section: Resultsmentioning
confidence: 99%
“…Heins, et al (9) found that during vegetative or early reproductive growth, neither con tinuous supplemental high intensity discharge (HID) lighting, nor 50% saran shading, influenced flower bud number. However, long term (30 day) Inc lighting reduced bud number (9). We note that temperatures were not lowered as reported by Roh and Wil kins (16) during floral initiation to possibly increase flower bud numbers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Information on quantitative relationships between the environment and rate of lily leaf unfolding is limited (9,17,18,22). Photosynthetic photon flux (PPF) and photoperiod have been shown to be minor factors affecting leaf unfolding rates and time of development (10,11). Grueber et al (9) reported on leaf unfolding rates for lilies forced in growth chambers for a wide range of temperatures; however, no functional relationship was presented.…”
mentioning
confidence: 99%